CCNA data center DCICT 200-155 official cert guide - Shamsee, Navaid; Klebanov, David; Fayed, Hesham; Afrose, Ahmed; Karakok, Ozden (Cisco Press, 2017)
CCNA Data Center DCICT 200-155 Official Cert Guide from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. A team of leading Cisco data center experts shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This is the eBook edition of the CCNA Data Center DCICT 200-155 Official Cert Guide. This eBook does not include the access code for the practice exam that comes with the print edition. This complete, official study package includes A test-preparation routine proven to help you pass the exam "Do I Know This Already?" quizzes, which enable you to decide how much time you need to spend on each section Part-ending exercises, which help you drill on key concepts you must know thoroughly Study plan suggestions and templates to help you organize and optimize your study time A final preparation chapter that guides you through tools and resources to help you craft your review and test-taking strategies Well regarded for its level of detail, study plans, assessment features, and challenging review questions and exercises, this official study guide helps you master the concepts and techniques that ensure your exam success. The official study guide helps you master topics on the CCNA Data Center DCICT 200-155 exam.
Includes index. - Online resource; title from title page (viewed February 6, 2017)
Keywords: Cisco Systems, Inc -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Computer networks -- Study guides -- Examinations; Cisco Systems, Inc; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Computer networks; Examinations; Electronic data processing personnel; Certification; Examinations; Study guides